Universal design for learning: Review and recommendations for EFL instruction - Timpe-Laughlin, Veronika; Laughlin, Michael K. (Inklusiver Englischunterricht. Impulse zur Unterrichtsentwicklung aus fachdidaktischer und sonderpädagogischer Perspektive, 2018)
Keywords: dept.hms

What’s Going on Out There? An exploration of K–12 PE Curricular Models and Content Taught in Public Schools - Hodges, Michael; Laughlin, Michael; Brusseau, Timothy (The Physical Educator, 2018)
Little is known about which curricular models and activity units are being taught in public schools. This exploratory study examined the K–12 physical education (PE) content and curricular models being implemented. Supervisors of PE recruited from one northeastern state participated in a 25-item questionnaire. Descriptive statistics and frequencies were calculated. Sixty-nine of 92 questionnaires were usable and included in the data analysis. Findings suggest that few districts were using a curricular model at the elementary (K–5) level (27%). Another common response of adopted curricular models at the elementary level was Movement Education (17.6%). At the secondary level, No Model (35%) and Fitness Education (25.6%) were common responses. Specific units such as volleyball, basketball, and weight training yielded the highest responses, while field hockey, golf, archery, lacrosse, and tennis yielded the fewest responses. The findings suggest that K–12 PE curricula may not reflect current trends and mandates. The key determinants could be a lack of curricular model use and heavy reliance upon activities known to present challenges toward standards-based education (i.e., softball). Perhaps K–12 PE and PE preparation programs can connect to effectively articulate a curriculum, and adopt and train on curricular approaches aiming to increase teacher effectiveness and reach national standards.Subscribe to TPE
Keywords: Content; Curricular Models; PETE; Units; dept.hms

Developing an Appropriate Goalball Unit for Secondary Physical Education - Laughlin, Michael K.; Happel, Kathleen (Strategies, 2016)
Goalball, a sport designed for those with visual impairments, is a competitive and recreational sport enjoyed by athletes around the world. Students with and without visual impairments can experience positive outcomes when teachers appropriately include a goalball unit as part of their inclusive secondary physical education curriculum. This article aims to help teachers identify these outcomes through strategies that encourage student success and appreciation for the sport. A framework to implement a goalball unit is provided along with strategies to target skill, tactical and game-play development.
Keywords: dept.hms

Deploying Video Analysis to Boost Instruction and Assessment in Physical Education - Laughlin, Michael K.; Hodges, Michael; Iraggi, Taylor (Journal of Physical Education, Recreation & Dance, 2019)
Physical educators are discovering the benefits of using video analysis to support their instruction and assessment. Slow-motion playback, zoom, and voice-over narration are just some of the features built into increasingly affordable mobile devices and applications that can easily be used by teachers to support student learning. Additionally, with the use of video technology, teachers are finding creative ways to provide instant motor-performance feedback which can be easily documented for assessment purposes. Yet, with any novel technology tool, internal and external challenges exist that may prevent teachers from realizing the myriad of benefits. This article provides a background on mobile video analysis tools, along with strategies to help physical educators discover ways to effectively implement this engaging technology into their curriculum.
Keywords: dept.hms; peer-reviewed

Effects of an adapted physical education training package on special education teacher instruction - Laughlin, Michael K.; Murata, Nathan M.; McDougall, Dennis (Behavioral Interventions, 2019)
This study investigated the impact of an adapted physical education training package on functional motor skill instruction of three special education teachers who instructed secondary students with low-incidence disabilities. The training package emphasized teachers' use of systematic prompting and specific reinforcement teaching strategies plus adapted physical education consultation. We used a multiple baseline design and collected data on the three teachers' use of systematic prompting and specific reinforcement plans during videotaped teaching trials. We also collected data on how teachers documented their instructional strategies, and we analyzed personal reflections that teachers wrote in the journals. Results indicated that with each of the three teachers, correctly implemented functional motor skill instructional performance improved after they completed the training package.
Keywords: dept.hms; functional motor skills; peer-reviewed; prompting; reinforcement; severe disabilities; special education

Assistive Technology: What Physical Educators Need to Know - Laughlin, Michael K., Murata ,Nathan M., Gonnelli ,Michele; and Larranaga, John (Journal of Physical Education, Recreation & Dance, 2018)
Assistive technology supplements and supports the learning of students with disabilities in school and at home. Thanks to federal mandates, students with disabilities receive consideration for assistive technology devices and services — the tools and supports needed to achieve determined learning outcomes. Assistive technology devices and services operate as a process, ensuring students with disabilities receive optimal access to learning across all educational settings and subject areas. This article provides physical educators with a working knowledge of the assistive technology process along with recommendations for supporting their students with disabilities.
Keywords: dept.hms